INTEGRATION INTELLIGENT TRANSPORTATION SYSTEMS INTO THE TRANSPORTATION PLANNING PROCESS - Gurinova, Jana (Doprava a spoje, 2005)
This paper discusses opportunities to integrate Intelligent Transportation Systems (ITS) into the transportation planning process. ITS refers to a variety of tools, such as traffic engineering concepts, software, hardware, and communications technologies, that can be applied in an integrated fashion to the transportation system to improve its efficiency and safety. ITS has a lot to offer in solving some of the most complicated transportation problems. Fundamentals of traditional transportation and ITS planning are introduced to show where these processes could be integrated.